ANALISIS PENGGUNAAN SERAT IJUK TERHADAP SIFAT MEKANIS BETON NORMAL - Koesoema, Hansen Chandra; Kushartono, Widodo (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2023)
Concrete is a mixture of cement, coarse aggregate, fine aggregate, water and or without admixture or additional mixed ingredients. There are various types of concrete, one of which is fibrous concrete. Fibrous concrete is a composite structure consisting of ordinary concrete and other materials in the form of fibers. In this research using a mixture of palm fiber with an average diameter of 0.24 mm. The treatment method is carried out by 5 days of immersion in water followed by steam for less than 5 hours. This research uses a volume variation of 1%, 2%, 3% with lengths of 2 and 3 cm palm fiber, respectively. Based on this research, it is known that the use of a mixture of palm fiber in concrete can increase the value of tensile strength and flexural strength with the addition of the percentage of palm fiber. the use of palm fiber mixed into concrete is produced by a length of 2 cm with a percentage of 1% with a percentage increase of 1.01% in compressive strength, a percentage of 2% with a percentage increase of 76.7% in tensile strength, and a length of 3 cm with a percentage of 3% with a percentage increase of 39.8% in flexural strength. Abstrak Beton merupakan campuran dari semen, agregat kasar, agregat halus, air, dan atau tanpa admixture atau bahan campuran tambahan. Ada bermacam macam jenis beton salah satunya beton berserat. Beton berserat merupakan bagan komposit yang terdiri dari beton biasa dan bahan lain yang berupa serat. Pada riset ini menggunakan campuran serat ijuk dengan diameter rata rata sebesar 0,24 mm. metode perawatan dilakukan dengan 5 hari perendaman dengan air dilanjutkan steam selama kurang 5 jam. Riset ini menggunakan variasi volume 1%, 2%, 3% dengan panjang serat ijuk berturut turut sepanjang 2 dan 3 cm. diketahui berdasarkan riset ini penggunaan campuran serat ijuk pada beton dapat meningkatkan nilai kuat tarik dan kuat lentur seiring penambahan persentase serat ijuk. penggunaan serat ijuk yang di campurkan ke dalam beton dihasilkan oleh Panjang 2 cm dengan persentase 1% dengan persentase peningkatan 1,01% pada kekuatan tekan, persentase 2% dengan persentase peningkatan 76,7% pada kekuatan tarik, dan Panjang 3 cm dengan persentase 3% dengan persentase peningkatan 39,8% pada kekuatan lentur.